City and Nation during Mass Displacement. Poland’s ‘Recovered Territories’ 1945–1948: The Case of Zielona Góra (Economic and Political Thought, 2024)
The immediate aftermath of the Second World War in Europe was marked by the displacementof millions of national groups in Central and Eastern Europe across newlyerected borders. These population movements altered the physical environment andethnic composition of the region. This article looks at one of these transfers in Poland’s„Recovered Territories” gained from Germany through post‑warpeace conferences,and its effect on the region’s cities. The article’s specific focus is how displacementaffected the medium‑sizedLower Silesian town of Zielona Góra. The article looks athow the Polish state and individual settlers in Zielona Góra claimed urban spaces astheir own whilst simultaneously eradicating signs of their former German inhabitants.Using newly opened archives and drawing on interviews conducted with displacedPoles it shows the development of nationalist and nationalising narratives in the cityand the problems the state had in implementing its visions there.
Keywords: Poland, Germany, displacement, Post‑Second World War, cities, state-building, Recovered Territories